Socialization of the Use of Online Land and Building Tax Services in Surabaya to the Community in Rungkut District - Pusvita, Noviyanti; Huda, Syamsul; Perdana, Putra (Unram Journal of Community Service, 2025)
Land and Building Tax has become one of the potential sources of state revenue in local tax income. However, despite its great potential, the realization of its collection still faces several obstacles, one of which is the low level of taxpayer compliance. Compliance will increase along with taxpayer satisfaction if tax services are made easier, more effective, and provided with greater service facilities by tax officers. The method used in this community service is an educational and hands-on approach, focused on socializing the use of the Surabaya Online Land and Building Tax service to the residents of Rungkut. This activity involves the delivery of theoretical material, followed by a direct demonstration of website usage. With the provision of this socialization, it can be seen that there has been a significant increase in the public's knowledge regarding the features and usage of the Surabaya online PBB service. The community also provided positive feedback and considered that the online Land and Building Tax service service is a very helpful advancement. with the presence of this online Land and Building Tax service, it can reach the entire community. Based on the results of the socialization of the online Land and Building Tax service that has been conducted in the Rungkut area, it turns out that many people have never used the Surabaya online Land and Building Tax service. Therefore, this socialization successfully opened their understanding of how to use it and what benefits they can gain from using it. With this, it is hoped that the community will become more aware of information regarding the Land and Building Tax